Part II - The Vila Nossa Senhora Aparecida Marginal Area Case-Study - Muzzarelli, Aurelio; Mourão Moura, Ana Clara; Arruda Silveira, Ivana; Nonato Saraiva, José (Cadernos de Arquitetura e Urbanismo, 2024)
Article originally published without abstract. Keywords assigned by the editorial team at the digitization.